Herodotus in context : ethnography, science, and the art of persuasion - Thomas, Rosalind, 1959- (Cambridge University Press, 2000)
"Herodotus called his work an enquiry and wrote before 'history' was a separate discipline. Coming from Halicarnassus, at the crossroads between the Persian and Athenian spheres of influence, he combined the culture of Athens with that of the more pluralistic and less ethnocentric cities of east Greece. Alive to the implications of this cultural background for Herodotus' thought, this study explores the much neglected contemporary connotations and context of the Histories, looking at them as part of the intellectual climate of his time. Concentrating on Herodotus' ethnography, geography and accounts of natural wonders, and examining his methods of argument and persuasion, it sees the Histories, which appear virtually without antecedents, as a product of the late fifth-century world of the natural scientists, medical writers and sophists - a world of controversy and debate."--Jacket